Neurobehavioral Mechanism of Cross-Education Phenomenon in the Upper Limb Based on Functional Near-Infrared Spectroscopy - PAN Yingying; WANG Menghuan; WANG Yixiu; XIE Min; JIANG Zhongli; LIN Feng (康复学报)
ObjectiveTo explore the neurobehavioral mechanism of cross-education phenomenon and asymmetry in the upper limb based on functional near-infrared spectroscopy (fNIRS).MethodsA total of 17 healthy subjects recruited by Sir Run Run Hospital of Nanjing Medical University from November 2023 to January 2024 were selected in a randomized cross-over trial. Purdue pegboard training with the contralateral upper limb of unilateral limb was taken as the contralateral training, and the number of Purdue pegboard plug-ins completed within a limited time as the task performance. fNIRS was used to collect the cerebral hemodynamic changes of healthy right-handed individuals after contralateral training when the left and right hand performed operational activities and record the behavioral data, and compare the cerebral cortex activation and behavioral performance of the left and right hands before and after contralateral training.ResultsAfter contralateral training, the performance of the left hand was significantly better than that before training (t=-8.865, P<0.010), while the performance of the right hand did not change after training (t=-1.689, P=0.606). In addition, the left pre-motor and supplementary motor area (CH 29), right pre-motor and supplementary motor area (CH 16, CH 17) and right primary motor cortex (CH 09) were more significantly activated after contralateral training when subjects performed the Purdue pegboard task with left hand (P<0.05). However, the right pre-motor and supplementary motor area (CH 19), right primary somatosensory cortex (CH 08) and right primary motor cortex (CH 10) showed a decreasing trend in the activation after contralateral training when subjects performed the Purdue pegboard task with right hand (P<0.05).ConclusionCross-education of the upper limbs is asymmetrical, indicating that the non-dominant hand experiences greater benefits compared to the dominant hand. Cross-education may be attributed to enhance the cortical activation of the bilateral pre-motor and supplementary motor area (pSMA) to improve the task performance of the non-training limb.